University Online Communication - Xenia Negrea (Social Sciences and Education Research Review)
Online communication has become a strategic component in building the university image in the context of the accelerated digitalization of higher education. This study aims to analyze how two Romanian universities – the University of Medicine and Pharmacy of Craiova (UMF Craiova) and the National University of Political Studies and Public Administration (SNSPA) – use digital media to communicate their institutional identity, attract audiences, and build relationships with stakeholders. The analysis is based on a qualitative content analysis of the official websites and social media accounts of the two institutions. The results reveal convergences in the use of online media, as well as important differences in storytelling, interactivity, and communication sustainability. The study is framed within the most recent theories of strategic university communication in the digital era.